Ambulance waiting and associated work flow improvement strategies: a pilot study to improve door-in-door-out time for thrombectomy patients in a primary stroke center. (13th July 2021) - Gaynor, Eva; Griffin, Emma; Thornton, John; Alderson, Jack; Martin, Mary; O'Driscoll, Anne; Daly, Patricia; O'Donnell, Cathal; Conroy, Ronan; O'Brien, Paul
Abstract : Background: Rapid access to thrombectomy for patients with large vessel occlusion (LVO) acute ischemic stroke (AIS) is critical for improving outcome. A major challenge for the 'drip and ship' model is reducing the door-in-door-out time (DIDO). We propose a new protocol with the aim of reducing DIDO, without adversely affecting emergency service usage time. Methods: Consecutive patients with suspected LVO AIS admitted to a Primary Stroke Center (PSC) from October 2018 to January 2021 were included. On arrival, the ambulance crew remained with the patient. Following immediate clinical and radiological evaluation, patients were transferred to the Comprehensive Stroke Center (CSC) by the same waiting crew. Key time metrics were collected and compared with historical data prior to the new protocol. Results: 27 patients had an LVO amenable for mechanical thrombectomy during the time period. There was a significant reduction in the DIDO times compared with the historical group (median 45 min vs 96 min; p<0.0001). There was no significant difference in ambulance usage time between the two time periods (median 53 min vs 45 min; p=0.530). There was an increase in ambulance usage time in FAST-positive patients not for transfer in the pilot group compared with FAST-positive patients not for transfer in the historical group (27 min vs 58 min; p<0.001). In addition, door-to-needle times (24 min vs 40 min; p=0.018) and door-to-CT times (11 min vs 25 min; p<0.0001) improved between the two groups. Conclusion: Our data show a significant reduction in the DIDO for patients transferred for thrombectomy, with no adverse effects on ambulance usage time.